Influencing the timing of parenteral nutrition initiation in the pediatric intensive care unit - Anderson CR; Lueckler J; Olson JA (Centro de Investigaciones y Publicaciones Farmaceuticas, 2019)
Background: Lack of benefit and potential harm of early parenteral nutrition (PN) initiation in critically ill children was highlighted in the 2016 published results of a large multicenter, randomized controlled trial. Objectives: The purpose of this project was to implement a process to delay PN initiation for up to five days after admission to our pediatric intensive care unit (PICU). Methods: Patients greater than thirty days of age, admitted to the PICU beginning July 1, 2016 were included in the analysis of the healthcare improvement initiative to decrease early PN initiation. A meeting was held with PICU fellows, attending physicians, dietitians, and pharmacists to reach a consensus to delay initiation of parenteral nutrition until PICU day five. The dietitian, with pharmacist support, reiterated recommendations on rounds and in formal notes. Results: A total of 2333 patients were identified in the pre-intervention group and a total of 2491 patients in the post-intervention group. The percentage of patients receiving PN prior to day five within the PICU was 5.5% in the pre-intervention group versus 3.1% in the delayed PN group (p<0.001). PICU patients receiving PN less than or equal to three days decreased from 2.6% pre-intervention to 1.5% post-intervention (p=0.01). For the subset of patients who were initiated on PN after admission to the PICU, median PICU length of stay was 7 days versus 6 days in the pre-intervention versus post-intervention group (p=0.26). Conclusions: Decrease in PN utilization was seen in the pre and post-intervention groups as assessed by percentage of patients initiated on PN prior to day five of PICU admission. Consensus among practitioners with consistent recommendations from the frontline dietitian and pharmacist, with nutrition support team collaboration, contributed to the evidence based quality initiative results. Delaying PN did not adversely affect length of stay pre versus post-intervention.